PENGARUH RELATIONSHIP MARKETING DAN SERVICE PERFORMANCE ERHADAP LOYALITAS NASABAH DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL MEDIASI (Studi Pada Nasabah Tabungan Bank Jateng Cabang Purbalingga) - Kefas Caesar Pradata; Siti Puryandani (Magister Manajemen STIE Bank BPD Jateng, 2022)
This study purpose to analyze the effect of relationship marketing and service performance on customer loyalty with customer satisfaction as a mediation. The sample in this study was customer savers at Bank JatengPurbalingga and taken as many as 100 respondents. The analytical tool used is Partial Least Square andhypothesis testing using t test, and mediation test using the Variance Accounted For method. The results of theanalysis show that there is an influence of relationship marketing and service performance on loyalty (p value0.000 and 0.001), there is an effect of relationship marketing service performance on customer satisfaction (pvalue each 0.000) and there is an effect of customer satisfaction on customer loyalty (0.000). Mediation analysis shows that satisfaction is able to mediate the influence of relationship marketing and serviceperformance on customer loyalty.